Another degrees reform: from 4+1 to 3+2 or 3+1+1 - Comalat, Maite; Abadal, Ernest (Anuario ThinkEPI, 2016)
The impact of the Spanish government decree RD 43/2015 on Library and Information Sciences studies is analyzed. The implementation of the European higher education area (EHEA) in Spain established the four-year bachelorís degree, a minority model in Europe, but very common in the rest of the world. Approval of RD 43/2015 opens the door to a three-year bachelorís degree and has been viewed with interest by some universities, especially in Catalonia. For LIS education, we can think in a 3 + 1 model, which includes the current bachelorís contents offering two titles (bachelor and master). On the other hand, it would be possible to create a two year masterís programs designed to meet the demands of graduates from other disciplines. The main drawback, in addition to fatigue from continuous changes in Spainís university education structure, is the need to ensure that the masterís first year has the same cost as one degree course.